Simulation modeling of a manufacturing process using Tecnomatix plant simulation software - Nurul Najihaha, .; Gebremariam, M. A.; Azmir, Azhari; Mulubrhan, Freselam (Penerbit UMP, 2021)
Industries in our community are under constant pressure and have high demands of customer orders for their products and there is the need to maximize the output for the same input of resources. In the case of lagging orders, it is very difficult for companies to manage and optimize the process flow for simultaneously coming orders. Process simulation can be suitably applied for studying and analyzing the system which can provide a framework for predicting and optimizing the process based on mathematical models. This work presents how to implement simulation tools in the real production planning so that an increase in the number of throughput in the time frame is achieved. The procedure starts with input data collection, data fitting, simulation model building, model validation, identification of the number throughput, and developed improvement system.